Most prevalent jobs of doctoral degree graduates by detailed field of study - Marc Frenette; Tomasz Handler (Economic and Social Reports)
Although it is well established that higher levels of educational attainment are generally associated with higher lifetime earnings (Frenette, 2019), and that this varies considerably by field of study (Ostrovsky and Frenette, 2014), less is known about the actual jobs held by graduates of specific disciplines. Understanding the relationship between field of study and occupation is important, as the type of work one does can play a considerable role in overall job satisfaction.